A Hard Oxide Semiconductor with A Direct and Narrow Bandgap and Switchable p–n Electrical Conduction. (27th October 2014) - Ovsyannikov, Sergey V.; Karkin, Alexander E.; Morozova, Natalia V.; Shchennikov, Vladimir V.; Bykova, Elena; Abakumov, Artem M.; Tsirlin, Alexander A.; Glazyrin, Konstantin V.; Dubrovinsky, Leonid
<x xml:space="preserve">Abstract</x> An oxide semiconductor (perovskite‐type Mn2O3) is reported which has a narrow and direct bandgap of 0.45 eV and a high Vickers hardness of 15 GPa. All the known materials with similar electronic band structures (e.g., InSb, PbTe, PbSe, PbS, and InAs) play crucial roles in the semiconductor industry. The perovskite‐type Mn2O3 described is much stronger than the above semiconductors and may find useful applications in different semiconductor devices, e.g., in IR detectors. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>